2023
DOI: 10.1007/s10648-023-09716-6
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Diagnostic Labels on the Evaluation of Students: a Multilevel Meta-Analysis

Abstract: Research suggests that children suffering from different types of disorders (learning disorders, behavioral disorders, or intellectual disabilities) are sometimes evaluated differently simply due to the presence of a diagnostic label. We conducted a multilevel meta-analysis of experimental studies (based on data from 8,295 participants and on 284 effects nested in 60 experiments) to examine the magnitude and robustness of such label effects and to explore the impact of potential moderators (type of evaluation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 130 publications
0
9
0
Order By: Relevance
“…In nonexperimental studies, Whitley (2010) and Shifrer (2013) showed that students labelled as learning disabled are less likely expected by their teachers to achieve a university degree than similar achieving but non-labelled students. In a recent meta-analysis about the effect of diagnostic labels on the evaluation of students, Franz et al (2023) distinguished between different types of assessments, such as behavioural evaluations, attitudes towards the child, evaluation of the personality and academic evaluations among others. They conclude that diagnostic labels for students negatively affect academic evaluations, including performance expectations and expectations of the academic future.…”
Section: Teachers' Expectations and The Learning Disability Labelmentioning
confidence: 99%
See 1 more Smart Citation
“…In nonexperimental studies, Whitley (2010) and Shifrer (2013) showed that students labelled as learning disabled are less likely expected by their teachers to achieve a university degree than similar achieving but non-labelled students. In a recent meta-analysis about the effect of diagnostic labels on the evaluation of students, Franz et al (2023) distinguished between different types of assessments, such as behavioural evaluations, attitudes towards the child, evaluation of the personality and academic evaluations among others. They conclude that diagnostic labels for students negatively affect academic evaluations, including performance expectations and expectations of the academic future.…”
Section: Teachers' Expectations and The Learning Disability Labelmentioning
confidence: 99%
“…However, labelling students risks exposing them to stereotypes, prejudice and discrimination. A recent metaanalysis found that Learning Disability (LD) labels for students have a negative impact on various teacher judgements of these students (Franz et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…More fundamentally, this concern could apply to any mental health diagnosis. For example, a meta-analysis of stigma associated with diagnostic labels in academic settings found no significant stigmatizing effects for behavioral disorders alone but did find effects for a combination of behavioral and emotional disorders (Franz et al, 2023). Despite any empirical evidence, assertions about stigma specific to ODD and CD contribute to an overall jaundiced and unfounded bias on the part of clinicians (e.g., Burke et al, 2022) that hinders sound assessment and diagnostic practice.…”
Section: Factors Affecting Clinical Judgment In the Assessment Of Dbdsmentioning
confidence: 99%
“…Sound studies on stigma would operationalize multiple types of potential stigmatization and would measure the real-world effects following the introduction of a diagnostic label. One concern evident in the existing research (e.g., Franz et al, 2023) is that some studies have characterized stigma to include a participant’s prediction of poor future academic functioning upon learning a diagnosis. In reality, such predictions would accurately reflect the empirical evidence that ODD and CD do predict increased risk for dropping out of school, higher rates of conflict with and rejection from school peers, and other types of impaired academic performance (e.g., Burke et al, in press).…”
Section: Factors Affecting Clinical Judgment In the Assessment Of Dbdsmentioning
confidence: 99%
“…This often opens the way to new, better collaboration between parents and teachers in organising optimal educational pathways for a child (Honkasilta et al, 2016). However, a mental disorder diagnosis also places the cause of experienced problems singlesidedly in the child and the child's brain, so that the child can easily experience (self-)stigma and feelings of inferiority (Batstra et al, 2012), under-perform as a consequence of teachers' lowered expectations (Franz et al, 2023;Metzger & Hamilton, 2021), and in the longer term, experience exclusion in education and in work (Ringbom et al, 2022). A second disadvantage of labelling school children with a mental disorder is that teachers attend less to contextual factors that may trigger problems in a child's behaviour or learning, once behaviours are given a mental disorder label.…”
Section: Introductionmentioning
confidence: 99%